HYPERBOLIC TYPE SOLUTIONS FOR THE COUPLE BOITI-LEON-PEMPINELLI SYSTEM - Yokus, Asif; Durur, Hulya; Ahmad, Hijaz (Univ Nis, 2020)
In this paper, the (1/G')-expansion method is proposed to construct hyperbolic type solutions of the nonlinear evolution equations. To asses the applicability and effectiveness of the method, two cases of the coupled Boiti-Leon-Pempinelli (CBLP) system have been investigated in this study. It is shown that, with the help of symbolic computation, the (1/G')-expansion method provides a powerful and straightforward mathematical tool for solving nonlinear partial differential equations.
Keywords: nonlinear evolution equations; partial differential equations; symbolic computation